Are there any circumstances in which logging primary wet-eucalypt forest will not add to the global carbon burden? - Dean, C; Wardell-Johnson, Grant; Kirkpatrick, J. (Elsevier BV, 2012)
Uncertainty associated with past land-use emissions restricts quantification of climate change effects. We identify the major affects of commercial forestry initiated over recent decades on Tasmanian primary-forest carbon (C), and search for means to mitigate its ongoing impacts. Spatio-temporal trends were derived from records of commercial operations combined with biomass data. Over the last two decades, the majority of forest C destined for short- or long-term emission (LTE, i.e. over several centuries and multiple harvests) was from clearfelling the higher-biomass wet-eucalypt forests on public land. Carbon dynamics at the unit-area-level for logging two disparate, wet-eucalypt forests were modelled. Parameters were varied to determine management options and model sensitivities under conversion by clearfell and intense burn to either eucalypt plantation or forest regeneration from local eucalypt seed. The first cycle of conversion of primary-forests contributed 43(±5)% to the LTE, and the LTE constituted ∼50% of the primary-forest C stock. Whether the first logging of even-aged primary-forests was prior to or after maturity, the LTEs were equivalent, although short-term emissions (STEs) were ∼2× higher from old-growth. Minor variations in soil organic carbon efflux during operations significantly altered LTEs. Conversion of wet-eucalypt by clearfell from 1999 to 2009 incurred an LTE of 2(±1.6) Tg from each year's logging. Lengthening the harvesting interval for sown forests from 80 to 200 years reduced LTEs by 42% and eucalypt wood-products by 26%; but yielded 40(±20) Mg ha−1 of C in rainforest understorey—helping to sustain mixed-forest ecosystems and their products. Using 200-yr cycles for the wet-eucalypt already clearfelled could avoid LTEs of ∼15 Tg. Long-term C dynamics under harvest cycles were constrained by mathematical precepts that facilitate climate change modelling, e.g. the time to reach the harvesting-cycle's asymptote is correlated to the half-life of the longer-lived C pool. Emissions are not recovered by sequestration in wood-products unless their half-lives are ∼10× contemporary values—requiring 200–1000 years for recovery, during which time emissions would augment global climate change. Emissions can be reduced by product substitution, and by recycling wood-products, in a stable wood market. Primary-forest is part of a global commons. Comprehensive C accounting cannot occur if logging effects are omitted.